Increased sink capacity enhances C and N assimilation under drought and elevated CO2 conditions in maize - ZONG, Yu-zheng; SHANGGUAN, Zhou-ping (Journal of Integrative Agriculture, 2016)
The maintenance of rapid growth under conditions of CO2 enrichment is directly related to the capacity of new leaves to use or store the additional assimilated carbon （C） and nitrogen （N）. Under drought conditions, however, less is known about C and N transport in C4 plants and the contributions of these processes to new foliar growth. We measured the patterns of C and N accumulation in maize （Zea mays L.） seedlings using 13C and 15N as tracers in CO2 climate chambers （380 or 750 μmol mol-1） under a mild drought stress induced with 10% PEG-6000. The drought stress under ambient conditions decreased the biomass production of the maize plants; however, this effect was reduced under elevated CO2. Compared with the water-stressed maize plants under atmospheric CO2, the treatment that combined elevated CO2 with water stress increased the accumulation of biomass, partitioned more C and N to new leaves as well as enhanced the carbon resource in ageing leaves and the carbon pool in new leaves. However, the C counterflow capability of the roots decreased. The elevated CO2 increased the time needed for newly acquired N to be present in the roots and increased the proportion of new N in the leaves. The maize plants supported the development of new leaves at elevated CO2 by altering the transport and remobilization of C and N. Under drought conditions, the increased activity of new leaves in relation to the storage of C and N sustained the enhanced growth of these plants under elevated CO2.